Multilateral development banks and financing for development: The role of resource needs reviews - Rishikesh Ram Bhandary; Kevin P. Gallagher; Maria Zucker-Marques; Maia Colodenco; Florencia Asef Horno (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
Multilateral development banks (MDBs) play a key role in providing developing countries with affordable, long-term finance. In 2024, to help meet development challenges, the G20 agreed on a roadmap to make the MDBs bigger, better and more effective and recommended MDBs conduct resource needs reviews to assess the adequacy of their resources to meet shareholder objectives and shared global challenges. This paper investigates the extent to which MDBs incorporate resource needs into their reviews of capital requirements. We find that MDBs generally do not have rigorous, evidence-based processes in place. Where they exist, the reviews have been ad hoc and focused on preserving the financial robustness of MDBs. Needs assessments exhibit path dependencies reflecting envelopes used in prior rounds. Our analysis is rooted in MDB documents, G20 communiqués, and case studies of MDBs. Forwardlooking resource needs assessments will be crucial to ensure that MDBs have the resources they need to support those objectives. The paper concludes with a set of principles that could govern resource reviews processes.
Keywords: F33; O19; H81; Q54; 330; multilateral development banks; G20; development finance; climate finance; development finance institutions